Serum 25-hydroxyvitamin D and the risk of stroke in Hong Kong Chinese - Leung, Raymond Y. H.; Han, Yi; Sing, Chor-Wing; Cheung, Bernard M. Y.; Wong, Ian C. K.; Tan, Kathryn C. B.; Kung, Annie W. C.; Cheung, Ching-Lung (Thrombosis and Haemostasis, 2017)
Low vitamin D levels have been associated with various cardiovascular diseases; however, whether it is associated with stroke remains inconclusive. We aimed to evaluate the association between serum 25-hydroxyvitamin D and risk of stroke. We conducted a cohort study consisting of 3,458 participants from the Hong Kong Osteoporosis Study aged ≥45 at baseline, examined between 1995 and 2010 and followed up using electronic medical records. Ischaemic and haemorrhagic stroke were defined using the ICD-9 code. In multivariable Cox-proportional hazard regression, quintiles 1 and 4 were significantly associated with increased risk of stroke when compared to the highest quintile (Quintile 1: HR, 1.78; 95 % CI, 1.16–2.74 and quintile 4: HR, 1.61; 95 % CI, 1.07–2.43). A similar association was observed in both men and women. In subgroup analysis, the association was specifically observed for ischaemic stroke, but not haemorrhagic stroke. Using a penalized regression spline, the association between vitamin D and risk of stroke was in a reverse J-shape, with the lowest risk of stroke being observed at 25(OH)D levels between 70 and 80 nmol/l. In conclusion, a low vitamin D level is associated with increased risk of ischaemic stroke; however, whether high vitamin D level is also associated with increased risk of stroke requires further study.Supplementary Material to this article is available at www.thrombosis-online.com.
Keywords: Stroke; vitamin D; epidemiological studies